Răspuns:
Explicație pas cu pas:
[tex]\Big(\frac{ {}^{ \sqrt{2}) } 3}{ \sqrt{2} } - \frac{5 \sqrt{2} }{4}\Big) - \Big( \frac{\not{18} \sqrt{2} }{\not6} + \frac{ \not{12}}{\not3 \sqrt{2} }\Big) \\ [/tex]
[tex] = \frac{ {}^{2)} 3 \sqrt{2} }{2} - \frac{5 \sqrt{2} }{4} - \Big(3 \sqrt{2} + \frac{ {}^{ \sqrt{2}) } 4}{ \sqrt{2} } \Big) \\ [/tex]
[tex] = \frac{6 \sqrt{2} }{4} - \frac{5 \sqrt{2} }{4} - \Big(3 \sqrt{2} + \frac{\not4 \sqrt{2} }{\not2} \Big) \\ [/tex]
[tex] = \frac{ \sqrt{2} }{4} - (3 \sqrt{2} + 2 \sqrt{2} ) \\ [/tex]
[tex] = \frac{ \sqrt{2} }{4} - {}^{4)} 5\sqrt{2} = \frac{\sqrt{2}}{4}- \frac{20\sqrt{2}}{4} = \boxed{- \frac{19 \sqrt{2}}{4}} \\ [/tex]